Comfortable driver's car seat fit parameter based on Malaysian anthropometrics data - Darliana Mohamad; Baba Md. Deros; Dian Darina Indah Darius; Norhidayah Fathirah Ramli; Ezrin Hani Sukadarin (http://ijph.tums.ac.ir/index.php/ijph/article/view/6162, 2015)
Previous studies found that driving posture discomfort can contribute to musculoskeletal disorders (MSDs), injuries, lumbar pain and fatigue. The three main objectives of this study were to identify the level of awareness for correct and safe driving posture, health implication to their body parts and to propose a suitable car seat fit dimensions appropriate for Malaysian drivers' population. The two methodologies used for the study conducted in 2014 were direct manual measurement of 62 anthropometric data involving 1312 subjects and using a survey questionnaire involving 136 subjects to perform subjective evaluation on driving posture discomfort based on 5 points Likert scale. Results showed 77% of the subjects that took part in the survey agreed that driving posture may influence their discomfort during driving. In short the car drivers were aware on the importance of correct and safe driving posture. However, they are still lacking in terms of knowledge and exposure to practice the correct posture. In add ition, survey respondents believed the body parts that experienced discomfort are the neck (50%), followed by the upper back (47.06%), lower back (45.59%), left buttock (39.71%), right buttock (38.97%), right shoulder (33.82%) and then the right foot ankle (23.53%). Drivers' awareness level and attitude toward correct and safe driving posture correlates positively to their physical health and comfort. Based on the Malaysian anthropometric data, this study has proposed a set of comfortable dimensions for driver's seat: backrest width (480 mm) and height (646 mm); cushion width (503 mm) and length (381 mm)